(Sub)millimetre dust polarization of protoplanetary discs from scattering by large millimetre-sized irregular grains. Issue 1 (18th January 2023) - Lin, Zhe-Yu Daniel; Li, Zhi-Yun; Yang, Haifeng; Muñoz, Olga; Looney, Leslie; Stephens, Ian; Hull, Charles L H; Fernández-López, Manuel; Harrison, Rachel
ABSTRACT: The size of dust grains, a, is key to the physical and chemical processes in circumstellar discs, but observational constraints of grain size remain challenging. (Sub)millimetre continuum observations often show a per cent-level polarization parallel to the disc minor axis, which is generally attributed to scattering by 100 μm -sized spherical grains (with a size parameter x ≡ 2π a /λ < 1, where λ is the wavelength). Larger spherical grains (with x greater than unity) would produce opposite polarization direction. However, the inferred size is in tension with the opacity index β that points to larger mm/cm-sized grains. We investigate the scattering-produced polarization by large irregular grains with a range of x greater than unity with optical properties obtained from laboratory experiments. Using the radiation transfer code, RADMC-3D, we find that large irregular grains still produce polarization parallel to the disc minor axis. If the original forsterite refractive index in the optical is adopted, then all samples can produce the typically observed level of polarization. Accounting for the more commonly adopted refractive index using the DSHARP dust model, only grains with x of several (corresponding to ∼mm-sized grains) can reach the same polarization level. Our results suggest that grains in discs can have sizes in the millimetre regime, which may alleviate the tension between the grain sizes inferred from scattering and other means. Additionally, if large irregular grains are not settled to the mid-plane, their strong forward scattering can produce asymmetries between the near and far side of an inclined disc, which can be used to infer their presence.